The reactive surface of Castor leaf [Ricinus communis L.] powder as a green adsorbent for the removal of heavy metals from natural river water - Martins, Amanda E. [UNESP]; Pereira, Milene S. [UNESP]; Jorgetto, Alexandre O. [UNESP]; Martines, Marco A.U.; Silva, Rafael I.V. [UNESP]; Saeki, Margarida J. [UNESP]; Castro, Gustavo R. [UNESP] (My University, 2013)
In this study, a green adsorbent was successfully applied to remove toxic metals from aqueous solutions. Dried minced castor leaves were fractionated into 63-μm particles to perform characterization and extraction experiments. Absorption bands in FTIR (Fourier Transform Infrared Spectroscopy) spectra at 1544, 1232 and 1350 cm-1 were assigned to nitrogen-containing groups. Elemental analysis showed high nitrogen and sulfur content: 5.76 and 1.93%, respectively. The adsorption kinetics for Cd(II) and Pb(II) followed a pseudo-second-order model, and no difference between the experimental and calculated Nf values (0.094 and 0.05 mmol g-1 for Cd(II) and Pb(II), respectively) was observed. The Ns values calculated using the modified Langmuir equation, 0.340 and 0.327 mmol g-1 for Cd(II) and Pb(II), respectively, were superior to the results obtained for several materials in the literature. The method proposed in this study was applied to pre-concentrate (45-fold enrichment factor) and used to measure Cd(II) and Pb(II) in freshwater samples from the Paraná River. The method was validated through a comparative analysis with a standard reference material (1643e). © 2013 Elsevier B.V. © 2013 Elsevier B.V. All rights reserved.
Keywords: Adsorbent; Aqueous samples; Castor leaf powder; Chemisorption; Metals ions; Adsorption kinetics; Comparative analysis; Enrichment factors; Pseudo-second order model; Reactive surfaces; Standard reference material; Adsorbents; Fourier transform infrared spectroscopy; Lead; Nitrogen; Powder metals; Adsorption